Degradation of Elastomer Damping Component for High-Speed Bearings - Anastasia Gaitanidou; Mario Tränkner; Georgios Iosifidis; Roberto DeSantis; Theofilos Efstathiadis; Anestis Kalfas (Engineering Proceedings)
The present paper studies the degradation of an ethylene propylene diene monomer (EPDM) due to aging within an environment resembling the conditions inside the turbine stage of an electrically assisted turbocharger for fuel cell applications, with a special focus on the influence of the system resonance. Aging experiments were conducted on EPDM O-rings of different thicknesses and compression levels, evaluating their degradation and determining its impact on system functionality. The study also quantified changes in system resonance and created an Arrhenius law-based forecast model. The unique activation energy for the degradation processes was identified, providing insight into the optimal dimension and compression of EPDM O-rings.